Research and Practice Analysis of Higher Vocational Colleges Facing the Experience and Dissemination of Regional Characteristic Tea Culture. (19th July 2022) - Yan, Xiangrong
Abstract : Tea culture has special relevance in China's cultural system. It is closely related to the development of tea industry. It is also an important branch of China's traditional cultural system. Therefore, it must be paid great attention to. Especially in the context of big data, computer technology is widely used in the links of culture or information communication, and its purpose is to improve the communication effect. Therefore, the dissemination of tea culture information can be realized with the help of computer technology. From this perspective, this paper analyzes the development of computer technology in the background of big data, summarizes the necessity of using computer technology in the dissemination of tea culture information and, on this basis, considers the application strategy of computer technology in the dissemination of tea culture information from the perspective of big data, hoping to enter a more ideal pattern of tea culture information dissemination.